A Christological approach to poverty in Africa: Following Christ amidst the needy - Verster, Pieter (HTS teologiese studies, 2015)
The serious challenges posed by poverty in Africa call for a new approach. A Christological approach to these issues inspires hope. A Christology from above, or ‘high’ Christology, has much to offer regarding God’s looking after humanity. Christ as the one for others humbled himself to give a life of fullness to the poorest and most ill, thereby bringing hope both for this life and for eternity. The approach followed should not lead to the exclusion of people, but rather to an endeavour to meet the challenge of brokenness. In societies where there is no hope left, the Christ of the wounded leads the way to new healing. Christ, verily God and verily human brings us before him in our totality, to be involved in all the needs of the community. The church should be the hands, feet and eyes of Christ for the needy.